2012
DOI: 10.1016/j.icarus.2012.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Dust release and tensile strength of the non-volatile layer of cometary nuclei

Abstract: a b s t r a c tWe developed a thermophysical model for cometary nuclei, which is based upon the assumption that comets form by the gravitational instability of an ensemble of dust and ice aggregates. Under this condition, the tensile strength of the ice-free outer layers of a cometary nucleus can be calculated, using the dust-aggregate collision and adhesion model of Weidling et al. (Weidling, R. et al. [2012]. Icarus, 218, 688-700). Based on available laboratory data on the gas permeability and thermal conduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
174
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(196 citation statements)
references
References 43 publications
21
174
0
1
Order By: Relevance
“…Experimental work by Weidling et al (2009) and Güttler et al (2009) also showed that the volume-filling factor of silica pebbles acquires a value of ∼0.4 after experiencing many bouncing collisions. The filling factor of the comet, φ c , is then the product of both: φ c = φ p × φ ≈ 0.24 (Skorov & Blum 2012). Comets are thus expected to be porous bodies, which agrees with recent density measurements and estimates (e.g.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Experimental work by Weidling et al (2009) and Güttler et al (2009) also showed that the volume-filling factor of silica pebbles acquires a value of ∼0.4 after experiencing many bouncing collisions. The filling factor of the comet, φ c , is then the product of both: φ c = φ p × φ ≈ 0.24 (Skorov & Blum 2012). Comets are thus expected to be porous bodies, which agrees with recent density measurements and estimates (e.g.…”
Section: Introductionsupporting
confidence: 86%
“…According to Skorov & Blum (2012), the packing fraction is φ P ≈ 0.6, which falls in the range between random loose packing (RLP) with φ P = 0.55 and random close packing (RCP) with φ P = 0.64.…”
Section: Dust-to-ice Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the thermal conductivity retrieved from observations might be treated as an upper limit for the solid conductivity of the surface layer. We assume that the solid conductivities of the dust crust and the ice-dust mixture are the same and that the material porosity is constant everywhere (as in Skorov & Blum 2012). In addition to the solid conductivity, the radiative conductivity as a part of the effective conductivity is considered in the model (Gundlach & Blum 2012).…”
Section: Depth Of Super-volatiles: Model Descriptionmentioning
confidence: 99%
“…If we assume that the pore diameter is about one millimeter and the tortuosity is about 3 (see references in Skorov & Blum 2012), then the expected escaping time is a few days. At the same time, diffusive resistance of the overlying layer is so high (it is proportional to the ratio of the depth to the pore diameter) that only a fraction of 100 ppm of sublimating molecules escapes, which means that the effective mass loss is very low.…”
Section: Transient Processes In a Gas-dust-ice Layermentioning
confidence: 99%